A novel sensitive microarray approach for differential screening using probes labelled with two different radioelements - Salin, H. (Oxford University Press, 2002)
We have developed a novel microarray approach for differential screening using probes labelled with two different radioelements. The complementary DNAs from the reverse transcription of mRNAs from two different biological samples were labelled with radioelements of significantly different energies ((3)H and (35)S or (33)P). Radioactive images corresponding to the expressed genes were acquired with a MicroImager, a real time, high resolution digital autoradiography system. An algorithm was used to process the data such that the initially acquired radioactive image was filtered into two subimages, each representative of the hybridisation result specific for one probe. The simultaneous screening of gene expression in two different biological samples requires <100 ng mRNA without any amplification. In such conditions, the technique is sensitive enough to directly quantify the amount of mRNA even when present in small amounts: 10(7) molecules in the probe as assessed with an added control sequence and 2 × 10(5) molecules with an endogenous tyrosine hydroxylase mRNA. This novel technique of double radioactive labelling on a microarray is thus suitable for the comparison of gene expression in two different biological samples available in only small quantities. Consequently, it has great potential for various biological fields, such as neuroscience.